Dose-dependent analgesic activity of mexiletine on thermally induced pain in rats - Patil, Aravind; Konda, Vijaya Chandra Reddy (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage. In spite of many advances in pain research, we are unable to deal in an effective way. The cost for new drug development is increasing day by day. Drug repurposing is an approach to look for new use in drugs that are already approved for other indications. Mexiletine is a sodium channel blockers that is being approved for treatment of arrhythmias. It is being tried in treatment of various painful conditions. The present study is to evaluate the dose-dependent analgesic activity of mexiletine with ibuprofen. Methods: The analgesic activity of mexiletine was compared at doses of 15mg/kg, 30mg/kg and 45mg/kg with the standard dose of ibuprofen at 10mg/kg in male Wistar rats in thermal model of tail flick analgesiometer. Results: At lower doses (15mg/kg) of mexiletine, analgesic activity of ibuprofen was significantly higher. At higher doses (30 mg/kg and 45 mg/kg) of mexiletine, it was observed that there is no significant difference between the analgesic activities of both drugs. Conclusions: Mexiletine demonstrated a dose-dependent analgesic activity. There was no statistically significant difference between the analgesic activities of higher doses of mexiletine when compared to ibuprofen.